Educational and social inequalities and cause-specific mortality in Mexico City: a prospective study - Addey, T; Alegre-Diaz, J; Bragg, F; Trichia, E; Wade, R; Gnatiuc Friedrichs, L; Lewington, S; Peto, R; Collins, R; Emberson, J (Elsevier, 2023)
Background: Social inequalities in adult mortality have been reported across diverse populations, but there is no largescale prospective evidence from Mexico. We aimed to quantify social, including educational, inequalities in mortality among adults in Mexico City.